Education and earnings growth: Evidence from 11 European countries - Giorgio Brunello; Simona Comi (Fondazione Eni Enrico Mattei (FEEM), 2000)
We use cohort data from 11 European countries to study whether experience profiles differ by educational attainment. Previous literature does not provide a clear answer to this question, that is important to evaluate private returns to education over the working life of individuals. We find evidence that employees with tertiary education have steeper experience profiles than employees with upper secondary or compulsory education. Hence, education provides not only an initial labour market advantage but also a permanent advantage that increases with time in the labour market. We also find that differences in earnings growth by education are lower in countries with a higher level of corporatism and higher in countries which have experienced both relatively fast labour productivity growth and a relatively low educational attainment. The educational system also seems to matter, because countries with a more stratified system o
Keywords: J30; 330; Education; earnings growth; Europe; Bildungsertrag; Lebenseinkommen; Bildungsniveau; Schätzung; EU-Staaten